2014
DOI: 10.1088/1742-6596/568/1/012018
|View full text |Cite
|
Sign up to set email alerts
|

NMR Studies of 3He Films on Boron Nitride

Abstract: Abstract.We report the results of NMR studies of the dynamics of 3 He adsorbed on hexagonal boron nitride. These studies can identify the phase transitions of the 2D films as a function of temperature. A thermally activated temperature dependence is observed for 2.6 < T < 8 K compared to a linear temperature dependence for 0.7 < T < 2.6 K. This linear dependence is consistent with that expected for thermal diffusion in a fluid for coverages of 0.4 -0.6 of a monolayer. IntroductionHelium-three monolayer and sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Our study is for 4 He, not 3 He, but at first sight those experiments seem in contradiction with our results because it is difficult to understand how 3 He could have a stable √ 3 × √ 3R30 • phase while we find that for the heavier mass 4 He such phase is unstable. A first comment is that the mentioned NMR measurements 25,26 give evidence that at a special coverage the 3 He atoms are in registry with those of hBN but there is no direct evidence that this ordered phase of 3 He corresponds indeed to a coverage of 1/3 of the adsorption sites as in the √ 3 × √ 3R30 • phase. On the basis of adsorption isotherms this NMR special coverage can be reconciled 28 with the √ 3 × √ 3R30 • phase only by advocating the presence of ill controlled strongly binding sites and edge effects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our study is for 4 He, not 3 He, but at first sight those experiments seem in contradiction with our results because it is difficult to understand how 3 He could have a stable √ 3 × √ 3R30 • phase while we find that for the heavier mass 4 He such phase is unstable. A first comment is that the mentioned NMR measurements 25,26 give evidence that at a special coverage the 3 He atoms are in registry with those of hBN but there is no direct evidence that this ordered phase of 3 He corresponds indeed to a coverage of 1/3 of the adsorption sites as in the √ 3 × √ 3R30 • phase. On the basis of adsorption isotherms this NMR special coverage can be reconciled 28 with the √ 3 × √ 3R30 • phase only by advocating the presence of ill controlled strongly binding sites and edge effects.…”
Section: Discussionmentioning
confidence: 99%
“…We are not aware of experimental study of the phase diagram of 4 He adsorbed on hBN while some studies have been performed for 3He [25][26][27] . From these NMR measurements the authors conclude that at low temperature 3 He forms an ordered state and this is identified as the √ 3 × √ 3R30 • phase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations